2005
DOI: 10.1086/431751
|View full text |Cite
|
Sign up to set email alerts
|

Radiative Hydrodynamic Models of the Optical and Ultraviolet Emission from Solar Flares

Abstract: We report on radiative hydrodynamic simulations of moderate and strong solar flares. The flares were simulated by calculating the atmospheric response to a beam of non-thermal electrons injected at the apex of a one-dimensional closed coronal loop, and include heating from thermal soft Xray, extreme ultraviolet and ultraviolet (XEUV) emission. The equations of radiative transfer and statistical equilibrium were treated in non-LTE and solved for numerous transitions of hydrogen, helium, and Ca ii allowing the c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
365
6
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 345 publications
(402 citation statements)
references
References 32 publications
(41 reference statements)
29
365
6
2
Order By: Relevance
“…Modelling of this line in a flare atmosphere should indicate if a direct mapping of centroid velocity to upper atmospheric velocity exists. A downward motion is expected in models of explosive chromospheric evaporation (Fisher et al 1985;Allred et al 2005), and has been observed previously in solar flares, including the optically thick He ii line which showed a similar magnitude of centroid shift as we observe in Mg ii (see Milligan & Dennis 2009 and references therein). Svestka et al (1980) and Ding et al (1995) discuss finding similarly shortlived downflows that were only associated with the outer edge of the ribbon.…”
Section: Discussionsupporting
confidence: 88%
“…Modelling of this line in a flare atmosphere should indicate if a direct mapping of centroid velocity to upper atmospheric velocity exists. A downward motion is expected in models of explosive chromospheric evaporation (Fisher et al 1985;Allred et al 2005), and has been observed previously in solar flares, including the optically thick He ii line which showed a similar magnitude of centroid shift as we observe in Mg ii (see Milligan & Dennis 2009 and references therein). Svestka et al (1980) and Ding et al (1995) discuss finding similarly shortlived downflows that were only associated with the outer edge of the ribbon.…”
Section: Discussionsupporting
confidence: 88%
“…This analysis allowed them to trace the behaviour of the Balmer continuum at λ < 3646Å and features of the line profiles both in weak and large flares. Observations in the blue spectral range agree well with both the two-temperature gas-dynamical modeling of an impulsive flare on the red dwarf (Katsova, Boiko, and Livshits, 1997) and the new single-temperature radiative hydrodynamic flare models by Allred et al (2005). The most important result of the analysis of these observations by Kowalski et al (2013) is the detection of two components of the flare optical continuum: blue continuum at the flare maximum that linearly decreases with wavelength from λ = 4000 − 4800Å, indicates the hot, black-body emission with typical temperatures of T BB ∼ 9000 − 14 000 K; the red continuum gives evidence for a T BB ∼ 8000 K component at the beginning of the gradual decay phase during eight flares, most of which are impulsive events.…”
Section: On a Model Of The Optical Continuum Source Of Superflaressupporting
confidence: 77%
“…A two-dimensional magnetic reconnection model called CSHKP (Carmichael 1964;Sturrock 1966;Hirayama 1974;Kopp & Pneuman 1976), suggests that the plasma surrounding a null point in the corona is heated such that high coronal pressure, thermal conduction, and non-thermal particles (mostly electrons) can efficiently carry energy from the magnetic reconnection site in the corona to the lower solar atmosphere along the magnetic field lines (Magara et al 1996). Thermal radiation from soft X-rays, EUV, and UV can also contribute to this process, but this contribution was found to be very small (Allred et al 2005). Other more recent works have raised questions about the viability of this mechanism in the light of recent observations (Fletcher & Hudson 2008) and suggested Alfvén wave propagation as an alternate energy transport mechanism from the corona to chromosphere during flares (Russell & Fletcher 2013).…”
Section: Introductionmentioning
confidence: 99%